ANALISIS EFEKTIVITAS SISTEM INFORMASI MANAJEMEN PENDIDIKAN DALAM MENINGKATKAN KINERJA ADMINISTRASI AKADEMIK - Novita Rolinsa Madina; Regi Mokodongan; Ria Anggita Zen (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
Introduction: This study examines the effectiveness of the Education Management Information System (EMIS) in improving academic administrative performance in Indonesian higher education institutions, considering the moderating role of human resource (HR) readiness. Methods: A mixed-methods approach was employed using Structural Equation Modeling Partial Least Squares (SEM-PLS) and in-depth interviews involving 285 respondents from 12 universities in North and Central Sulawesi. Results: The findings reveal that system quality, information quality, service quality, user satisfaction, and actual use significantly influence academic administrative performance (p < 0.05). HR readiness was found to positively moderate these relationships, while the proposed model explained 71.3% of the variance in administrative performance. Conclusion: Integrating EMIS quality dimensions with HR readiness enhances academic administration effectiveness and provides a contextal model for higher education governance in Indonesia.